2019
DOI: 10.1093/carcin/bgz064
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin involves in chronic stress-evoked melanoma metastasis via β-arrestin 2-mediated ERK signaling pathway

Abstract: Stress is associated with an increased risk of lung metastasis in melanoma. However, the underlying mechanism is elusive. Oxytocin (OXT), a neurohormone produced by the hypothalamus, plays a vital role in laboring induction and lactation. Emerging evidence suggests that OXT also regulates human emotions, social cognition, social behaviors and stress-related disorders. Here, we reported that a significant up-regulation of oxytocin receptors (OXTRs) was observed in malignant melanoma. The activation of OXTRs dra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
(40 reference statements)
0
17
0
1
Order By: Relevance
“…Breast cancer remains the most common cancer in women worldwide and metastasis is widely accepted as the major cause for cancer death 4 , 5 . In breast tumor bearing mice model, psychosocial stress could induce the formation of pre-metastatic niches in distant organs 6 9 , while blocking stress-associated hormone factors could reduce the metastasis 10 , 11 . Previous clinical research also indicated that stress-related factors are involved in promoting breast cancer progression 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer remains the most common cancer in women worldwide and metastasis is widely accepted as the major cause for cancer death 4 , 5 . In breast tumor bearing mice model, psychosocial stress could induce the formation of pre-metastatic niches in distant organs 6 9 , while blocking stress-associated hormone factors could reduce the metastasis 10 , 11 . Previous clinical research also indicated that stress-related factors are involved in promoting breast cancer progression 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The link between GPCR/β-arrestins complexes and cancer is an established concept ( 41 ) and seems to be result of sustained intracellular signaling occurring upon dysregulation of intracellular β-arrestin protein levels ( 42 ). These molecules were associated with drug resistance of breast ( 43 ) and lung cancer cells ( 44 ), cancer cell migration and invasion ( 45 ), tumor progression ( 46 ) and metastasis ( 47 ), as well as a number of other tumors ( 48 ). Thus, β-arrestins were proposed as a target for therapeutic strategies ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating between signaling events that occur pre or post β-arrestin recruitment has become an important focus 3234 for studies looking at understanding the (patho)physiological roles of β-arrestin-mediated receptor internalization, desensitization and trafficking 35,36 . In addition, β-arrestin-dependent signaling has been linked to chronic stress-evoked melanoma metastasis via OTR 37 , increased neonatal rat cardiac fibroblast proliferation via V 1a R 38 , morphine tolerance via V 1b R 39 and sustained non-canonical signaling after receptor internalization via V 2 R, resulting in strong antidiuretic and anti-natriuretic effects 40 . Biased ligands such as I8-arachnotocin discovered in this work are thus important tools to advance our understanding in these areas of interest.…”
Section: Discussionmentioning
confidence: 99%